EFEKTIVITAS PEMBERIAN PENGUATAN (REINFORCEMENT) TERHADAP MOTIVASI BELAJAR SISWI KELAS XII IPA MA AL-AMIEN PRAGAAN SUMENEP - Abd. qadir (Institut Dirosat Islamiyah Al-Amien Prenduan, 2019)
Reinforcement is a form of response that is part of the modification of teacher behavior to student behavior, which aims to provide information or feedback for students One way that educators can apply in increasing student learning motivation is by providing reinforcement. This research is a quantitative research consisting of two variables, namely the method of providing reinforcement (variable X) and learning motivation (variable Y). And the data collection technique is by distributing questionnaires for variables X and Y, and observation as a support for the questionnaire, while the subjects of this study were taken from 40 respondents. For data analysis, the data used is a price table and a conservative size table then the hepotesis test uses a product moment correlation coefficient test. The influence of reinforcement has a positive influence on the learning motivation of Class XII science MA students. Al-Amien I Pragaan academic year 2016/2017. The effect of reinforcement on the learning motivation of class XII science MA students. Al-Amien I Pragaan academic year 2016/2017 included sufficient correlation.